Improved the coconut shell biochar properties for bio-electricity generation of microbial fuel cells from synthetic wastewater - Junjira Thipraksa; Pimprapa Chaijak (Journal of Degraded and Mining Lands Management, 2022)
A microbial fuel cell (MFC) is a green device that utilizes chemical energy in organic materials to generate electricity. The low-cost electrode used in this study was made from agricultural waste, coconut shells. The electrochemical properties were improved by combining oxidizing agents and microwave heating processes. The modified coconut shell electrode outperformed virgin biochar by 30.89-fold (230.13±10.11 m2/g). The maximum open-circuit voltage, current density, and power density are respectively 995.00±5.00 mV, 841.67±14.43 mA/m2, and 283.42±9.67 mW/m2. This study demonstrated that modified coconut shell biochar could be used as a low-cost alternative electrode for electricity generation.